2022
DOI: 10.1016/j.profnurs.2021.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Stress and depression in undergraduate students during the COVID-19 pandemic: Nursing students compared to undergraduate students in non-nursing majors

Abstract: Background The COVID-19 pandemic exacerbated an already alarming mental health crisis on college campuses. Nursing students were uniquely impacted through the loss of clinical practicum experiences. Purpose The purpose of this study was to explore relationships between student perceptions of life-stress and depressive symptoms during the COVID-19 pandemic in nursing students compared to students in other academic disciplines. A secondary purpose of this study was to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 41 publications
(47 reference statements)
2
29
0
3
Order By: Relevance
“…College students with depression usually felt hopeless and helpless [7], and adverse childhood experiences (ACEs) were recognized as long-distance risks of depression in adulthood [8,9]; smartphone addiction [10,11] and epidemic [12,13]are also important causes of depression among college students, depression and race of college students [14], gender [15], and professional [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…College students with depression usually felt hopeless and helpless [7], and adverse childhood experiences (ACEs) were recognized as long-distance risks of depression in adulthood [8,9]; smartphone addiction [10,11] and epidemic [12,13]are also important causes of depression among college students, depression and race of college students [14], gender [15], and professional [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Even before the pandemic, nursing students experienced higher levels of stress than non‐nursing students 18 . These rates increased during the COVID‐19 pandemic 18–20 . In one study, rates of high stress increased sixfold, while rates of moderate‐to‐severe anxiety and depression increased 3‐4‐fold 18 .…”
Section: Discussionmentioning
confidence: 99%
“…The pandemic has created opportunity for us to change the stressful culture of clinical nursing education and move towards creating a nurturing learning environment for students, as participants in our study appreciated informal check-ins from nursing instructors via group text and mass email to offer support and encouragement. Black Thomas (2022) found that the cohort structure of nursing education programs may support academic success through a sense of belonging. We have learned that online group discussion forum postings at regular intervals (e.g., weekly) related to health, well-being, and self-care could be strategically posted by a nursing instructor to the cohort of students as a means of support.…”
Section: Discussionmentioning
confidence: 99%
“…There have been calls to improve the structure of clinical nursing education to make the transition into nursing practice easier for nursing students and to enable them to feel more prepared to enter the workforce of the complex healthcare environment ( Black Thomas, 2022 ; Hawkins et al, 2019 ; Kavanagh & Sharpnack, 2021 ; Simpson & Sawatzky, 2020 ; Wang et al, 2019 ). To date, most decisions about the nature and length of clinical placements have been made based on historical decisions and pragmatic constraints of healthcare partners rather than evidence ( Kardong-Edgren et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%